Blood pressure response to dynamic exercise testing in adolescent elite athletes, what is normal? - Wuestenfeld, J.C.; Baersch, F.; Ruedrich, P.; Paech, C.; Wolfarth, B. (Frontiers in Pediatrics, 2022)
Background: In general, only few studies are dedicated to blood pressure behavior under stress in children and adolescents. Even less is published about the blood pressure behavior of young high-performance athletes on the ergometer. For this reason, we evaluated the blood pressure behavior under stress compared to non-athletes in a large collective (n=739) of young high-performance athletes (age 10-20 years, mean 15.8 years, male 442, female 297) of different sports. A complete echocardiographic examination was available in all athletes. Result: Regardless of gender, the young competitive athletes achieved significantly higher maximum blood pressure values than those in previously studies investigated populations (male 193±23/81±8mmHg, female 177±19/79±9mmHg. Based on the data obtained, blood pressure percentiles are now defined explicitly for junior athletes across sports as well as age- and gender-dependent, which did not exist in this form of normal values for the special clientele of young competitive athletes. The echocardiographic examinations demonstrated stress-induced cardiac adaptation symptoms in the majority of athletes, which thus correlate with the comparatively higher stress blood pressures compared to non-athletes. Conclusion: For the first time, blood pressure percentiles for exercise tests on the ergometer for age groups and gender in high performance athletes are defined based on a comparatively large collective of young competitive athletes. Upper limits were determined, in particular for systolic blood pressure under stress, and categorized according to gender and age. Performance diagnosticians and physicians are now enabled to make a more accurate assessment of the corresponding blood pressure regulation of young athletes under exercise conditions.